1986
DOI: 10.1111/j.1365-2265.1986.tb03283.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LHRH Treatment on Testicular Descent and Hormonal Response in Cryptorchidism

Abstract: In a double-blind placebo-controlled study in 49 boys with cryptorchidism the effect of intranasal synthetic LHRH was studied. After 8 weeks improvement in testicular location was found in 13 testes (37%), but this improvement was considered sufficient of only six testes. Placebo resulted in an improved location in 18% of the testes. The mean change in testicular position (expressed in cm) after LHRH therapy was slightly greater than after placebo but only in the squatting position did this difference reach si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…25,26 Three studies were of good quality, 17,23,25,26 2 were of fair quality, 14,15 and 9 were of poor quality. [9][10][11][12][13]16,[18][19][20][21][22]24 Six studies 9-16 specifically compared successful testicular descent rates after administration of LHRH versus placebo (2 fair quality 14,15 and 4 poor quality [9][10][11][12][13]16 ). Five of 6 studies concluded that LHRH was more effective than placebo in inducing testicular descent with variable reported effect sizes across studies, whereas 1 study was equivocal (see Table 2).…”
Section: Effectiveness Of Hormones For Achieving Testicular Descentmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Three studies were of good quality, 17,23,25,26 2 were of fair quality, 14,15 and 9 were of poor quality. [9][10][11][12][13]16,[18][19][20][21][22]24 Six studies 9-16 specifically compared successful testicular descent rates after administration of LHRH versus placebo (2 fair quality 14,15 and 4 poor quality [9][10][11][12][13]16 ). Five of 6 studies concluded that LHRH was more effective than placebo in inducing testicular descent with variable reported effect sizes across studies, whereas 1 study was equivocal (see Table 2).…”
Section: Effectiveness Of Hormones For Achieving Testicular Descentmentioning
confidence: 99%
“…Five of 6 studies concluded that LHRH was more effective than placebo in inducing testicular descent with variable reported effect sizes across studies, whereas 1 study was equivocal (see Table 2). [12][13][14][15][16] In the 5 studies that appeared to show a benefit to LHRH therapy, 4 did not assess statistical significance at all, whereas 1 failed to document statistical significance likely because of inadequate sample size. No harms of hormonal treatment were reported.…”
Section: Effectiveness Of Hormones For Achieving Testicular Descentmentioning
confidence: 99%
“…In this respect the distance between a transverse plane through the pubic tubercle and the testicular midpoint has been proposed (Scorer -1964;Hosli -1971;Karpe et al -1983;Wit et al -1985). In this respect the distance between a transverse plane through the pubic tubercle and the testicular midpoint has been proposed (Scorer -1964;Hosli -1971;Karpe et al -1983;Wit et al -1985).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect the distance between a transverse plane through the pubic tubercle and the testicular midpoint has been proposed (Scorer -1964;Hosli -1971;Karpe et al -1983;Wit et al -1985). Measurements of this distance have also been used to quantify the effect of intranasally administered LHRH (Luteinizing Hormone-Releasing Hormone) (Karpe et al -1983;Wit et al -1985). Measurements of this distance have also been used to quantify the effect of intranasally administered LHRH (Luteinizing Hormone-Releasing Hormone) (Karpe et al -1983;Wit et al -1985).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1975 (14), luteinizing hormone-releasing hor¬ mone (LHRH) has been given in a nasal spray with promising results at first; later, this treatment did not prove to be successful (15,16).…”
mentioning
confidence: 99%